EFFECTIVENESS OF MODIFIED BUHNER’S TECHNIQUE USING INFUSION (DRIP) SET TUBING IN COWS SUFFERING FROM PROLAPSE - BHATTACHARYYA, H K; BUCHOO, B A; FAZILI, M R (The Indian Journal of Animal Reproduction, 2011)
Thirty four cows presented for the treatment of prolapse (uterine, 19 and vaginal, 15) were included in this study. The prolapsed mass was replaced following standard technique. Modified buhner’s suture was applied using sterile infusion set as suture material. It resulted in persistent retention without recurrence in all the cows. Complications and disfigurement of the vulva was not noticed even in cases where suture was removed after a prolonged period.